'Evidence for waterborne origin of an extended mixed gastroenteritis outbreak in a town in Northern Greece, 2019'. (9th December 2020) - Tzani, M.; Mellou, K.; Kyritsi, M.; Kolokythopoulou, F.; Vontas, A.; Sideroglou, T.; Chrysostomou, A.; Mandilara, G. D.; Tryfinopoulou, K.; Georgakopoulou, T.; Hadjichristodoulou, C.
Abstract: We investigated a large gastroenteritis outbreak that occurred in Northern Greece in 2019. A case was defined as anyone presenting with diarrhoea and/or vomiting from 24 January 2019 to 04 February 2019. We conducted a case-control study (CCS) using random selection of participants >16 years of age, residents of town X, who visited the health care centre between 25 and 28 January 2019. Moreover, we conducted a retrospective cohort study (CS) at the four elementary schools of the town. We collected clinical and water samples and the water supply system was inspected. In total, we recorded 638 cases (53% female; median age was 44 years (range 0–93)). Forty-eight cases and 52 controls participated in the CCS and 236 students in the CS. Both CCS and CS indicated tap water as the most likely source (OR 10, 95% CI 2.09–93.4, explaining 95.7% of cases; RR = 2.22, 95% CI 1.42–3.46, respectively). More than one pathogen was detected from stool samples of 6 of the 11 cases tested (norovirus, Campylobacter jejuni, Enterohemorrhagic E. coli (EHEC) and Enteropathogenic E. coli (EPEC)). Water samples, collected after ad-hoc chlorination, tested negative. Technical failures of the water tanks' status were identified. Our results suggested a waterborne outbreak. We recommended regular monitoring of the water supply system and immediate repair of technical failures.